Loading Effect of Sol-Gel Derived Barium Hexaferrite on Magnetic Polymer Composites - Thanida Charoensuk; Wannisa Thongsamrit; Chesta Ruttanapun; Pongsakorn Jantaratana; Chitnarong Sirisathitkul (My University, 2021)
Solution–processing methods were investigated as viable alternatives to produce the polymer-bonded barium hexaferrite (BaM). BaM powders were first synthesized by using the sol-gel auto-combustion method. While the ignition period in two synthesis batches varied, the morphology of hexagonal microplates and nanorods, as well as magnetic properties, were reproduced. To prepare magnetic polymer composites, these BaM powders were then incorporated into the acrylonitrile-butadiene-styrene (ABS) matrix with a weight ratio of 80:20, 70:30, and 60:40 by using the solution casting method. Magnetizations were linearly decreased with a reduction in ferrite loading. Compared to the BaM loose powders and pressed pellet, both remanent and saturation magnetizations were lower and gave rise to comparable values of the squareness. The squareness around 0.5 of BaM samples and their composites revealed the isotropic alignment. Interestingly, the coercivity was significantly increased from 1727–1776 Oe in loose BaM powders to 1874–2052 Oe for the BaM-ABS composites. These composites have potential to be implemented in the additive manufacturing of rare-earth-free magnets.
Keywords: Barium ferrite; Acrylonitrile butadiene styrene; Barium; Magnetic Properties and Synthesis of Ferrites